The effect of SMS reminders on health screening uptake: a randomized experiment in Indonesia - Marcus, Maja E.; Reuter, Anna; Rogge, Lisa; Vollmer, Sebastian (Discussion papers, 2021)
While the burden of non-communicable diseases is rising in low- and middle-income countries, the uptake of screening for these diseases remains low. We conducted a community-based RCT in Indonesia to assess whether personalized and targeted text messages can increase the demand for existing public screening services for diabetes and hypertension in the at-risk population. Our intervention increased screening uptake by approximately 6.6 percentage points compared to the pure control group. Among those, who received and read the messages, the effect size is 17 percentage points. The intervention appears to work through a reminder rather than a knowledge effect. We conclude that text messages can be a cheap and easily scalable tool to reduce testing gaps in a middle-income country setting.